Preservice Teachers’ Reflective Practice and Self-Directed Learning in Teaching Practicum Experience: A Mixed-Methods Study - Thammaprateep, Jurarat; Chartisathian, Chanipun (วารสารวิชาการมหาวิทยาลัยราชภัฏภูเก็ต, 2025)
This mixed-methods study explores the role of reflective practice in fostering self-directed learning (SDL) among preservice teachers during their fully online teaching practicum experience. The study involved 230 students enrolled in the Graduate Diploma Program in Curriculum and Instruction at Sukhothai Thammathirat Open University. Data collection methods included pre- and post-practicum administration of the Self-Directed Learning Questionnaire (SDLQ), reflective journals (n=187), and semi-structured interviews (n=12). The quantitative data were analyzed using descriptive statistics and the qualitative data were analyzed from journals and interviews, which were subjected to thematic analysis. Quantitative results showed a consistent increase in motivation, self-monitoring, and self-management after the practicum. Thematic analysis of qualitative data revealed that structured reflection facilitated through teaching videos, mentor feedback, and peer interaction contributed significantly to SDL development. Contextual factors in the teaching practicum such as digital supervision platforms and structured self-assessment frameworks were also found to enhance engagement and personal growth. The findings emphasized the importance of integrating reflective practice into teacher education programs to build autonomy, metacognition, and professional identity aligned with lifelong learning.